Aflatoxins Occurrence, Detection and Novel Detoxification Strategies - Claude Assaf, Jean (IntechOpen, 2022)
Aflatoxins are produced by fungi on agricultural crops. They contaminate foods and feeds worldwide and are a threat to humans and animals. They can occur at any stage from pre- to post-harvest, including transportation and storage. This book discusses aflatoxins with chapters on occurrence and prevalence, contamination exposure, toxicology and control in foods and feeds, immunosuppressive actions, hazards and regulations, detection methods, effects of climate change, novel detoxification strategies, and legislations.